Unicity of Meromorphic Functions Sharing Sets with Their Linear Difference Polynomials - Sheng Li; BaoQin Chen (Abstract and Applied Analysis)
We mainly investigate the unicity of meromorphic functions sharing two or three sets with their linear difference polynomials and prove some results.